Responsabilidad Social Corporativa y Calidad de Vida Laboral como Determinantes de la Identificación Organizacional y la Intención de Rotación: Evidencia del Sector Bancario Angoleño (Research, Society and Development, 2026)
This study aims to analyze the influence of Corporate Social Responsibility (CSR) and Quality of Work Life (QWL) on Organizational Identification (OI) and Turnover Intention (TI) in the Angolan banking sector. A quantitative approach was adopted, based on a sample of 120 employees from banking institutions, selected through a non-probabilistic convenience sampling technique, considering participants’ accessibility and availability. Data were collected through a structured questionnaire and subsequently analyzed using IBM SPSS Statistics software, enabling the application of descriptive and inferential statistical analyses to assess the relationships among the variables under study. The results show that positive perceptions of CSR practices and high levels of QWL are significantly associated with increased Organizational Identification. Employees who recognize socially responsible practices and favorable working conditions tend to develop a stronger sense of belonging, value alignment, and organizational commitment. However, a notable contradiction was observed: despite high levels of QWL and OI, turnover intention remained high, and no statistically significant relationship was found between OI, QWL, and TI. These findings suggest that turnover intention may be influenced by additional contextual factors, such as economic conditions and professional expectations. This study contributes to the literature by contextualizing these relationships within the Angolan context, reinforcing the importance of organizational policies focused on employee well-being and sustainability.